Expanding the International Baccalaureate Diploma Programme in Japan: The Role of University Admissions Reforms. (April 2018) - Sanders, Justin; Ishikura, Yukiko
In 2011, the Japanese government, in partnership with the International Baccalaureate (IB) Organization, embarked on an ambitious agenda of increasing the number of schools offering the IB Diploma Programme (DP) in Japan. One of the biggest challenges in this initiative is improving the recognition of the IB Diploma as an acceptable and sought after qualification for entry into the nation's higher education institutions. By examining data on DP student matriculation and a survey of Japanese university admissions offices, this paper explores the relationship between the government project, growth of the DP and admissions reform in Japan. Analysis suggests that while the DP recognition situation in Japan is changing, the pace is fairly gradual compared to the timeline set by the government, and there is still some way to go to meet the project targets. Additionally, it appears to be the private universities rather than the national universities that are leading in the reforms and accepting the most DP students.